ANALISIS PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE MELALUI ATTITUDE TOWARD USING PADA APLIKASI SEGARI - Rachman, Arief Iman; Naeli Umniati (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim: This research aims to determine the influence of perceived usefulness and perceived ease of use on behavioral intention to use the sugar application through an Attitude toward using among sugar consumers in the Jakarta, Depok, Tangerang, and Bekasi areas. Method: This research uses quantitative methods with a survey research type. Sampling used a non-probability sampling technique with a purposive sampling type. Research Finding: Behavioral intention to use the Segari application is influenced by perceived ease of use and perceived usefulness with attitude toward using it as an intervening variable. Theoretical contribution: This research shows that perceived ease of use and perceived usefulness with an attitude toward using it as an intervening variable are very effective in increasing interest in using the Segari application. Practitionel implication: The implication of this research for companies is to continue to pay attention to and improve the Segari application in terms of ease of use by carrying out promotions, publications, and outreach to users to increase interest in using the application. Research limitation: The results obtained are not entirely consistent with the findings of previous studies, especially on the relationship between Perceived Usefulness and Attitude toward using, as well as Perceived ease of use on Behavioral intention to use, which indicates the possibility of the influence of other external factors that have not been analyzed further.